The Effects of the Real Exchange Rate Volatility and Misalignments on Foreign Trade Flows in Uzbekistan - Ulugbek Olimov; Nishanbay Sirajiddinov (Kiel Institute for the World Economy (IfW), 2008)
This study documents a quantitative analysis of exchange rate volatilities and misalignment in Uzbekistan for the period of 1994q3-2005q2. The results suggest that the real exchange rate volatility and misalignment have depressing effects on the volume of trade, mainly exports in Uzbekistan. The Government's currency rationing policy was lessening the volatility proving that the policy-induced changes in exchange rate has a stabilizing effect on trade flows. The implied elasticity for the most significant real exchange rate volatility coefficient is -0.20. Using a two-step Engle-Granger technique import demand and export supply price elasticities are computed. The results are consistent with the predictions from a number of previous studies, and in particular, the estimated exports price elasticity for Uzbek economy ranges from 1.65 to 1.84, while import demand price elasticity is between -0.78 and -0.83. At the same time, relatively lower elasticity during 'the currency rationing' period indicate that large devaluations, most likely, did not generate the expected improvements in the overall export performance.
Keywords: C32; F41; 330; Real exchange rate; volatility; misalignment; trade flows; Uzbekistan; Kaufkraftparität; Volatilität; Wechselkurssystem; Außenwirtschaft; Usbekistan